Iodine Chemisorption, Interpenetration and Polycatenation: Cationic MOFs and CPs from Group 13 Metal Halides and Dipyridyl Linkers - Schäfer, Thomas C.; Becker, Jonathan; Seuffert, Marcel T.; Heuler, Dominik; Sedykh, Alexander E.; Müller‐Buschbaum, Klaus (Chemistry : a European journal, 2022)
Invited for the cover of this issue are Klaus Müller‐Buschbaum and co‐workers at Giessen University. The image depicts an aluminium‐based MOF as a novel material for the capture of iodine radioisotopes from a potential gas atmosphere exposure. Read the full text of the article at 10.1002/chem.202104171. “One MOF is highly functional and a bridge between open fundamental science and application relevant for an environmental problem.” This and more about the story behind the front cover can be found in the article at 10.1002/chem.202104171).